Contra el anhelo apocalíptico – en defensa de una esperanza práctica en tiempos de crisis - Against Apocalyptic Longing - In Defense of a Practical Hope in Times of Crisis - Farahat, Anuscheh (2020)
This work analyzes the way out of the coronavirus crisis as a question that admits various possibilities that have to be developed by political action. Based on this premise and establishing a comparison with the euro crisis, the author stresses that the way out of the crisis must be social. She then goes on to discuss the difficulties of structuring solidarity at the transnational level. And, finally, it analyzes the need for the State Constitutions to maintain their capacity as a normative orientation framewo
Keywords: coronavirus crisis; politics; euro crisis; social crisis; solidarity; transnationality; state constitutions